Strategi Peningkatan Pertanian melalui Sosialisasi Pupuk Organik dan Budidaya Indigofera di Desa Sukawening, Kabupaten Bogor - Zaenal Abidin; Aushafa Dyazra; Zaki Maharani; Cika Hilda Fransiski; Dyo Dion Dewantara; Elsa Amelya Fitriany; Muhamad Luthfi Asyidiq; Muhamad Zidan Rahmat; Neng Rahayu Novita; Nur Hafifah; Nur Hanifah; Riska Nurul Putri; Sheila Gracia Ginting (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Sustainable agriculture is the management of agricultural business resources to help changing human needs while maintaining or improving the quality of the environment and conserving natural resources. One example is "Organic Agriculture" with the use of compost. However, the lack of knowledge of farmers in making compost makes many people are still reluctant to use the fertilizer. This is the background of the holding of the socialization of compost making among farmers in Sukawening Village. This socialization activity was carried out to educate farmers about making compost and minimizing agricultural waste in Sukawening village and the introduction of Indigofera plants to farmers and residents of Sukawening. This activity was carried out in Sukawening Village, Bogor District. The making of compost fertilizer is done on February 26, 2020. The method of socialization used is the provision of material directly and discussion sessions. This socialization began with preparations for the implementation of activities, then continued with the dissemination of information and demonstrations on making compost fertilizer. The reduced forage has an impact on the feeding and quality of feed to livestock. Indigofera sp. is a forage plant that can produce well in the dry season and in the rainy season and can be used as a substitution of forage for animal feed where Indigofera sp. contains various substances that are beneficial for livestock. Socialization regarding Indigofera sp. conducted at 'Dosen Mengabdi' Program (Lecturer Subserve Program). Submission of material includes the steps of planting, fertilizing, maintaining, harvesting, to the stage of developing business partnerships. From the demonstration of fertilizer manufacturing and the socialization of Indigofera sp. The people of Sukawening Village are aware of the importance of using organic fertilizer in an effort to create sustainable agriculture. Keywords: compost fertilizers, indigofera, organic agriculture, socialization.